Intelligent transmit power control algorithm for the multi-user interference of wireless network - Xianchao ZHANG; Yao ZHAO; Haijun YE; Rui FAN (Tongxin xuebao)
To deal with the inter-user interference problem in wireless networks, an intelligent transmit power control scheme was proposed to manage the inter-user interference and guarantee multiple users' quality of service.Firstly, considering the complex dynamic wireless channel environment, a transmit power control model that aims to maximize the weighted sum-rate of the wireless communication system was established.Then, an intelligent power control algorithm based on the actor-critic framework in deep reinforcement learning was designed to shorten the power control decision time.Simulation results show that the proposed algorithm converges quickly, and when there are 10 pairs transceivers, the computation time consumed by the intelligent power control method is only a quarter of the time consumed by the traditional optimal algorithm.